Editorial - Pasierbek, Wit (Horyzonty Wychowania, 2017)
Sincethebeginningofhisexistence,manhasincessantly beengrapplingwiththeexperienceandknowledgeofthesubject: what is good and what is wrong. This most contrasting reality touches the deepest spheres of human being: his morality – justifiedorfalsechoices,hisrelationswithothers–creatingreality of happiness or hatred and finally, structures of social life. Because, what is good gives man a sense of happiness, confidence,joyandhopefulaimingatfulfillinghisownhumanity,thus lifetothefull.Whereasbadthingsseemtocontradictitdefinitely. Evillimitsman,makeshimsad,encloseshimwithintheboundariesofpowerlessnessandinconsequencedestroys his positive struggle leading him to the future of death. And what is interesting:goodandevil,whichseemtohaveanexternalnatureto man, thanks to his actions they assume personal forms.